Oral administration of Lactobacillus brevis KB290 to mice alleviates clinical symptoms following influenza virus infection. (6th November 2013) - Waki, N.; Yajima, N.; Suganuma, H.; Buddle, B.M.; Luo, D.; Heiser, A.; Zheng, T.
Abstract Lactobacillus brevis KB290 (KB290), isolated from a traditional Japanese pickle 'Suguki', has been reported to have immunomodulatory effects. We investigated whether oral administration of KB290 has protective effects against influenza virus (IFV) infection in mice. After 14 days of administration of lyophilized KB290 suspended in phosphate‐buffered saline by oral gavage, BALB/c mice were intranasally infected with 2 × MLD50 (50% mouse lethal dose) of IFV A/PR/8/34 (H1N1). Prophylactically administered KB290 significantly alleviated the loss of body weight and the deterioration in observational physical conditions induced by the infection. In addition, 7 days after infection, the levels of IFV‐specific immunoglobulin (Ig)A in bronchoalveolar lavage fluid were significantly increased in mice fed KB290 compared with controls. Moreover, there was a significant elevation of serum interferon (IFN)‐α in KB290 group mice, even at three and 7 days after infection, despite the administration of KB290 being stopped before IFV infection. Our results demonstrated that oral administration of KB290 before infection could alleviate IFV‐induced clinical symptoms. Alleviation of clinical symptoms by KB290 consumption may have been induced by long‐lasting enhancement of IFN‐α production and the augmentation of IFV‐specific IgA production. Significance and Impact of the Study This study demonstrated that oral administration of Lactobacillus brevis KB290 (KB290), a probiotic strain derived from a Japanese traditional pickle, could protect against influenza virus (IFV) infection in mice. Our results demonstrated that continual intake of KB290 for 14 days prior to IFV infection alleviated clinical symptoms such as loss of body weight and deterioration in observational physical conditions induced by the infection. The beneficial effects of KB290 consumption may have been elicited by the long‐lasting enhancement of interferon‐α production and the augmentation of IFV‐specific immunoglobulin A production.